Kajian terhadap Jenis dan Tata Urutan Peraturan Perundang-undangan Indonesia - Author: Syihabudin (Jurnal Hukum IUS QUIA IUSTUM, 2003)
Kind and procedural regulation oflaws managed in determining No. lll/MPR/2000 on Law Resource and Procedural regulation oflaws contain some problem. Through this discussion, the writer shows some basic problem deals with the kind and procedural regulation of laws. Accordance with the task ofthe People's Consultative Assembly to criticize the material and the law status of determination ofthe People's Consultative Assembly (MPR/S) issued sine 1966-2002, The People's Consultative Assembly (MPR) at the General Council 2003, classifies The Determinations into groups, as written in The People's Consultative Assembly Determination No. 1/MPf^2003 on searching the material and law determination status ofthe People's Consultative Assembly Determination (MPRS) and MPR 1960-2003. The People's Consultative Assembly Determination grouped the Determination No.lll/MPR/2003 as a The People's ConsultaWe Assembly Determination valid until Constitution established. The following writing is expected to be material of discussion in forming the Laws as the replacement ofThe People's Consultative Assembly.